Regionalização e Planejamento no Rio Grande do Norte - Jane Roberta de Assis Barbosa; Diego Tenório Paz; Aldo Dantas (Confins)
The article analyzes the regionalizations produced by the State of Rio Grande do Norte during the years of 1960 and 1970, which constitutes a baseline for the current planning. The work shows that while taking these regionalizations as reference to direct their actions, primarily for the pole cities, the State helped to mask problems and difficulties related to the use of the territory. For the analysis were used six documents, namely: 1) Polarized Regions of Rio Grande do Norte (1968); 2) Structural Diagnosis of the State – Rio Grande do Norte (1975); 3) PPA-RN 2004-2007; 4) PPA-RN 2008-2011; 5) PPA-RN 2012-2015; 6) PPA-RN 2016-2019. The cartography produced and the analytical bases used, resulted in the definition of two types of regions in the territory of Rio Grande do Norte: Regions of Necessary Action (RNAs) and Regions of Priority Action (RPAs), which are expressed in maps  formulated from the use of the free software PhilCarto. Its production considered the territory used as category of analysis and the Human Development Index Municipal (IDHM) as key variable.